3R Based Learning Method (Reuse, Reduce, Recycle) In Enhancing Early Childhood Creativity - Hawila Rassi; Taroci Neolaka; Ariyanti Tafuli; Merianus Maifani; Debora Kamuilut; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
Background: Creativity is a fundamental aspect of early childhood development because it enables children to generate original ideas, solve problems, and express themselves through meaningful learning experiences. The 3R-Based learning method (Reuse, Reduce, Recycle) has emerged as an innovative and environmentally friendly instructional approach that encourages children to explore, reuse, and recycle materials while fostering creativity and environmental awareness. However, empirical evidence regarding its implementation in authentic early childhood education settings remains limited. Objective: This study aimed to analyze the effect of the 3R-Based learning method on the creativity of children aged 4–5 years at PAUD Cahaya Pasar Tani Kolhua. Method: This quantitative study employed an ex post facto research design involving 25 children selected through total sampling. Data were collected using questionnaires measuring the implementation of the 3R-Based learning method and children's creativity and were analyzed using descriptive statistics and simple linear regression. Results: The findings revealed that the 3R-Based learning method had a positive and statistically significant effect on children's creativity (p = 0.002; p < 0.05). The coefficient of determination (R² = 0.342) indicated that the method explained 34.2% of the variance in children's creativity, while 65.8% was influenced by other factors. Novelty: This study provides empirical evidence of implementing the 3R-Based learning method through an ex post facto design in an authentic early childhood education setting by integrating environmental sustainability with creativity development. Conclusion: The 3R-Based learning method can effectively support early childhood creativity by providing meaningful, exploratory, and environmentally oriented learning experiences.